2017
DOI: 10.1002/mus.25394
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit number estimation and neuromuscular fidelity in 3 stages of sarcopenia

Abstract: Unlike MU number estimates, strength and MU stability differed across groups and related to degree of sarcopenia. Muscle Nerve 55: 676-684, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…The elbow extensor torque of the older men was approximately 50% lower than that of the young participants; however, similar levels of voluntary activation were achieved. Although we cannot assess the independent contribution of the anconeus to elbow extensor torque and we did not measure muscle volume, it is reasonable to expect that overall extensor weakness is the result of general muscle atrophy and other related factors . In addition to MU loss, there are other nonneurological factors that could contribute to sarcopenia.…”
Section: Resultsmentioning
confidence: 97%
“…The elbow extensor torque of the older men was approximately 50% lower than that of the young participants; however, similar levels of voluntary activation were achieved. Although we cannot assess the independent contribution of the anconeus to elbow extensor torque and we did not measure muscle volume, it is reasonable to expect that overall extensor weakness is the result of general muscle atrophy and other related factors . In addition to MU loss, there are other nonneurological factors that could contribute to sarcopenia.…”
Section: Resultsmentioning
confidence: 97%
“…A recent study compared TA motor unit numbers in groups described as pre‐sarcopenic, sarcopenic and severe sarcopenic (Gilmore et al . ). In agreement with our findings for TA, they found that motor unit numbers were similar across groups.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas some studies suggest that lifelong high‐intensity physical activity, such as running, may minimize the loss of motor units associated with ageing in the biceps brachii and tibialis anterior, others showed that tibialis anterior motor units were not spared in older adults athletes . Moreover, it is unclear whether sarcopenia is associated with reductions in motor unit number …”
Section: Physiological Systems That Contribute To the Decline In Eldementioning
confidence: 99%